Bempedoic acid in the management of lipid disorders and cardiovascular risk. 2023 position paper of the International Lipid Expert Panel (ILEP) - Banach, Maciej; Penson, Peter E; Farnier, Michel; Fras, Zlatko; Latkovskis, Gustavs; Laufs, Ulrich; Paneni, Francesco; Parini, Paolo; Pirro, Matteo; Reiner, Željko; Vrablik, Michal; Escobar, Carlos (Progress in cardiovascular diseases, 2023)
Cardiovascular disease (CVD) is a chronic non-communicable disease (NCD) and the predominant cause of morbidity and mortality worldwide. Substantial reductions in the CVD prevalence have been achieved in recent years by the attenuation of risk factors (particularly hypertension and dyslipidaemias) in primary and secondary prevention. Despite the remarkable success of lipid lowering treatments, and of statins in particular, in reducing the risk of CVD, there is still an unmet clinical need for the attainment of guideline lipid-targets in even 2/3 of patients. Bempedoic acid, the first in-class inhibitor of ATP-citrate lyase presents a new approach to lipid-lowering therapy. By reducing the endogenous production of cholesterol, upstream of the rate-limiting enzyme HMG-CoA-reductase, i.e., the target of statins, bempedoic acid reduces circulating plasma concentrations of low-density lipoprotein cholesterol (LDL-C), and major adverse CVD events (MACE). Bempedoic acid has the potential to contribute to the reduction of CVD risk not only as monotherapy, but even further as part of a lipid-lowering combination therapy with ezetimibe, reducing LDL-C cholesterol up to 40%. This position paper of the International Lipid Expert Panel (ILEP) summarises the recent evidence around the efficacy and safety of bempedoic acid and presents practical recommendations for its use, which complement the 'lower-is-better-for-longer' approach to lipid management, which is applied across international guidelines for the management of CVD risk. Practical evidence-based guidance is provided relating to the use of bempedoic acid in atherosclerotic CVD, familial hypercholesterolaemia, and statin intolerance. Although there are still no sufficient data avilable for the role of bempedoic acid in the primary prevention of CVD, its favourable effects on plasma glucose and inflammatory markers makes this drug a rational choice in the patient-centred care of specific groups of primary prevention.
Keywords: cholesterol; LDL-cholesterol; Heart Disease Risk Factors; Cholesterol, LDL; anticholesteremika; lidé; statiny; Cholesterol; Risk Factors; Anticholesteremic Agents; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Cardiovascular Diseases; ETC1002; Atherosclerotic cardiovascular disease; rizikové faktory; kardiovaskulární nemoci; Bempedoic acid; rizikové faktory kardiovaskulárních chorob; Humans